Assessing targeted macroprudential financial regulation: The case of the 2006 commercial real estate guidance for banks - Bassett, William F.; Marsh, W. Blake (Journal of Financial Stability, 2017)
In January 2006, federal regulators issued guidance requiring banks with specific high concentrations of commercial real estate (CRE) loans to tighten managerial controls. This paper shows that banks with concentrations in excess of the thresholds set in the guidance subsequently experienced slower growth in their CRE portfolios than can be explained by changes in bank or economic conditions. Moreover, banks above the CRE thresholds tended to have slower commercial and industrial loan growth but faster household loan growth following issuance of the guidance. The results highlight the potentially broad influence that portfolio-based macroprudential regulation might have on bank behavior.